Firm performance through online engagement: The role of experience and customer inspiraton - Alreesh, M. (2021)
This research aims to assess the current status of online trade relations between Kuwait and Portugal. To do so, we examine how firm managers from Portugal and Kuwait use online platforms to engage customers to enhance firm performance. A set of existing constructs was chosen (Online Experience, Customer Inspiration, Online Customer Engagement, Firm Performance, National Culture), which were included in a proposed model of structural equations, in order to assess the contribution of Online Experience and Customer inspiration to the current status of online trade relations (through Online Customer Engagement), and how these can be improved to the further development of e-commerce between the two countries